Juncus kuohii (Juncaceae), a new species from Taiwan - Jung, Ming-Jer (Phytotaxa, 2013)
Juncus kuohii, a new species from the central mountain range of Taiwan, is described and illustrated. It is comparedmorphologically to similar Juncus species in neighboring regions. An updated artificial key to Juncus species in Taiwanis also included.